Extraction and composition analysis of flavonoids in peony seed shells - ZOU Ping; ZHANG Ying-yang; ZOU Lin-ling (Shipin yu jixie)
Objective: To extract natural flavonoid compounds （MDZK） from peony seed husks for composition analysis and antioxidant research. Methods: The total flavonoids of peony seed shell were extracted by solvent reflux extraction method. The ultraviolet-visible spectrophotometer method was used to determine the MDZK content and antioxidant properties; The total flavonoids extracted were analyzed by LC-MS method. Results: When the solvent was 70% ethanol, the extraction temperature was 70 ℃, the feed-to-liquid ratio was 1∶25 （g/mL）, and the extraction time was 60 min, the MDZK yield was the highest, which was （10.54±0.13）%. When the concentration of MDZK reached 120 μg/mL, the highest clearance rates of DPPH radicals, O2 radicals and ·OH radicals were 58.54%, 55.72% and 49.07%, respectively, which showed that MDZK had certain antioxidant effects and good effects. More than 20 flavonoid compounds and their derivatives were identified by comparison with the database, of which the most abundant content were Luteoloside, Eriodictyol Kaempfero, Apigenin and Neohesperidin. Conclusion: The flavonoid compounds in the shell of peony seeds have good antioxidant activity and can be used as antioxidant products in food industry or medicine, and have wide application prospects.